Immunomodulatory activity of glycodelin: implications in allograft rejection. (18th January 2018) - Dixit, A; Balakrishnan, B; Karande, A A
Summary: Glycodelin is an immunomodulator, indispensable for the maintenance of pregnancy in humans. The glycoprotein induces apoptosis in activated CD4 + T cells, monocytes and natural killer (NK) cells, and suppresses the activity of cytotoxic T cells, macrophages and dendritic cells. This study explores the immunosuppressive property of glycodelin for its possible use in preventing graft rejection. Because glycodelin is found only in certain primates, the hypothesis was investigated in an allograft nude mouse model. It is demonstrated that treatment of alloactivated mononuclear cells with glycodelin thwarts graft rejection. Glycodelin decreases the number of activated CD4 + and CD8 + cells and down-regulates the expression of key proteins known to be involved in graft demise such as granzyme-B, eomesodermin (EOMES), interleukin (IL)-2 and proinflammatory cytokines [tumour necrosis factor (TNF)-α and IL-6], resulting in a weakened cell-mediated immune response. Immunosuppressive drugs for treating allograft rejection are associated with severe side effects. Glycodelin, a natural immunomodulator in humans, would be an ideal alternative candidate. Graphical Abstract: